Access to Justice through Legal Aid in Nigeria: An Exposition on Some Salient Features of the Legal Aid Act - Adebayo, Akintunde Abidemi; Ugowe, Anthonia Omosefe (Faculty of Law, Universitas Brawijaya, 2019)
According to Black’s Law Dictionary, justice is the fair and proper administration of law. Similarly, access to justice is the ability to make use of the courts and other relevant institutions to efficiently protect and enforce rights. Access to justice is imperative in every society. People will access justice only if the proper situation creates. In a bid, to remove this major barrier in accessing justice, the Legal Aid Council of Nigeria was established in 1976. The concept of legal aid means the provision of free legal services to the indigent and underprivileged members of the society. Its importance and cannot be overemphasized particularly considering the level of illiteracy and poverty which are considered on the high side in Nigeria. Hence, in 2011, the Legal Aid Act 2011 was enacted. The birth of the Act repealed the old Act. This article analyses 3ethe provisions of both Acts with emphasis on the innovations of the new Act to promote access to justice and concludes with recommendations. Concerning the Council, it finds that there is a need for better funding and engagement of more salaried lawyers in order to enable it to carry out its functions as the Council is grappling with the challenge of underfunding and recruitment of more hands to work towards the achievement of its set objectives, among others.